2013
DOI: 10.3389/fnbot.2013.00014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of social intention on movement kinematics in cooperative actions

Abstract: Optimal control models of biological movements are used to account for those internal variables that constrain voluntary goal-directed actions. They, however, do not take into account external environmental constraints as those associated to social intention. We investigated here the effects of the social context on kinematic characteristics of sequential actions consisting in placing an object on an initial pad (preparatory action) before reaching and grasping as fast as possible the object to move it to anot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
66
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(79 citation statements)
references
References 46 publications
13
66
0
Order By: Relevance
“…For example, by changing the presence of an observer, along with the observer’s proximity and their ability to intervene in the participant’s action, Quesque et al (2013) found that the kinematic parameters of participants’ object-directed actions (in particular preparatory actions) were significantly altered. This was true even in cases where it was impossible for the observer to directly influence the action outcome.…”
Section: The Importance Of Interactionmentioning
confidence: 99%
“…For example, by changing the presence of an observer, along with the observer’s proximity and their ability to intervene in the participant’s action, Quesque et al (2013) found that the kinematic parameters of participants’ object-directed actions (in particular preparatory actions) were significantly altered. This was true even in cases where it was impossible for the observer to directly influence the action outcome.…”
Section: The Importance Of Interactionmentioning
confidence: 99%
“…Scientific objectives Recent kinematic studies have shown that social context shapes action planning (Becchio, Sartori, & Castiello, 2010;Quesque, Lewkowicz, Delevoye-Turrell, & Coello, 2013). Moreover, we observed in a previous study that humans are able to discriminate between actions performed under different social contexts: reach for a cup for my own use or reach for a cup to give it to someone else .…”
Section: Reinforcement Learningmentioning
confidence: 97%
“…Here, we describe an example of a very simple face-to-face interactive paradigm in which two human agents exchange an object while trying to earn the most rewards possible. This software solution was used to run the study that is reported in Quesque et al (2013); it was also used to test the integration of eyetracking and 3-D movement capture .…”
Section: Reinforcement Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent researches in cognitive psychology have suggested that even in that case movement kinematics is affected. In particular, these studies showed that when we perform an action with a social instead of a personal intention, we amplify the spatial and temporal parameters of the motor action [11]. Furthermore, an observer is able to perceive these kinematic deviants and anticipate social intention in motor actions performed by others, in order to act in a complementary way ( [9]; see [10] for a review).…”
Section: Introductionmentioning
confidence: 99%